2021
DOI: 10.1101/2021.01.23.427909
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sexual dimorphism in outcomes of non-muscle invasive bladder cancer: a role of CD163+ M2 macrophages, B cells and PD-L1 immune checkpoint

Abstract: Non-muscle invasive bladder cancer (NMIBC) is significantly more common in men than women. However, female patients with NMIBC often present with more aggressive disease and do not respond as well to immunotherapy treatments. We hypothesized that sexual dimorphism in the tumor immune microenvironment (TIME) may contribute to the inferior clinical outcomes observed in female patients. To test this hypothesis, we interrogated the expression patterns of genes associated with specific immune cell types and immune … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(45 reference statements)
1
0
0
Order By: Relevance
“…Although the differences were nominally significant, we observed a higher amount of IGK expression in females. Similarly, a recent finding reported an increased expression of immune checkpoint genes, and those associated with B-cell recruitment and function, in high-grade bladder cancer tumors from females compared to those from males (39). Interestingly, we observed approximately 40-fold differences between tumor and normal samples regarding the number of IG reads.…”
Section: Discussionsupporting
confidence: 78%
“…Although the differences were nominally significant, we observed a higher amount of IGK expression in females. Similarly, a recent finding reported an increased expression of immune checkpoint genes, and those associated with B-cell recruitment and function, in high-grade bladder cancer tumors from females compared to those from males (39). Interestingly, we observed approximately 40-fold differences between tumor and normal samples regarding the number of IG reads.…”
Section: Discussionsupporting
confidence: 78%
“…Consistently, in cervical cancer and oral carcinomas, high levels of CD163+ TAMs infiltration were also associated with worse disease-free survival (DFS) [10,30,31]. Accumulated evidence suggests that a higher CD163+ TAMs count indicates poor prognosis and high metastatic potential in various cancers [32]; however, how CD163 works in the protumoral activation of TAMs remains unclear. Our data showed that the infiltration levels of M2-TAMs were significantly associated with Gleason score and the prognosis of PCa patients.…”
Section: Discussionmentioning
confidence: 98%